Ultrasonographic evaluation of portal hypertnsion - Ahamed, MS; Chowdhury, PK; Mohiuddin, AS; Hossain, MA; Paik, B (Mediscope, 2015)
A descriptive type of cross-sectional study was done to measure diameters of splenic, superior mesenteric and portal veins with their variation with respiration in patients with portal hypertension. Trans-abdominal ultrasonography was used for the purpose among purposively selected 59 patients with chronic liver disease and portal hypertension using computer sonography with multiple probes having multiple frequency depending on physical built of subjects. The diameters of selected veins were measured in the course of expiration and deep inspiration. Mean age of respondents was 53.2 years with standard deviation of 11.4 years. 44 (74.6%) subjects were male, whereas 15 (25.4%) were female. In all cases oesophageal varices were present. Portal vein was clearly visualized in all cases, while splenic vein in 53 (89.8%) cases and superior mesenteric vein in 49 (83.1%) cases. During deep inspiration, diameter of portal vein was greater than 13 mm in 31 (52.5%), while ?13 mm in 28 (47.5%) of portal hypertensive cases. Of 31, lack variation in diameter during respiration was observed in 29 (93.6%) cases. Size of liver (length in mid-clavicular line) in 18 (30.5%) cases were between 96 to 115 mm, while in 19 (32.2%) cases it was within 116 to 135 mm and in 22 (37.3%) cases it was between 136 to 160 mm. In 36 (61.0%) cases surface of liver was irregular, while in 51 (86.4%) cases parenchymal echotexture of liver was coarse. Size of spleen was enlarged in 44 (74.6%) cases, and ascites was present in 47 (79.7%) cases. Diameter variation with breathing of splenic and superior mesenteric veins observed only in 5 (8.5%) patients. Lack of diameter variation of portal, splenic and superior mesenteric veins with respiration in ultrasonography is an indicator of portal hypertension. Mediscope Vol. 2, No. 1: 2015, Pages 27-31